Thermal wrinkling of liquid crystal polymer shell/core spheres. (October 2020) - Xu, Fan; Zhao, Shichen
Abstract: Smart soft materials that can flexibly respond to external multi-physics stimuli, have shown intriguing applications in shape-morphing and morphology control. Here, we present tunable wrinkling patterns in core–shell spheres under thermal load via controlling the orientation of director in nematic liquid crystal polymer (LCP). To analyze nonlinear instability and morphological evolution of LCP shell/core spheres, we develop a shallow core–shell model that accounts for director-induced anisotropic spontaneous strains. By tuning the alignment of liquid crystal director, we explore effects of anisotropy of spontaneous strains on wrinkling pattern formation and evolution. When the director is along the out-of-plane direction, the surface shell undergoes equi-biaxial expansion, resulting in hexagonal, checkerboard, herringbone or labyrinth pattern, determined by a single dimensionless parameter C s which characterizes the stiffness ratio and curvature of the system. Moreover, stability analysis yields an analytical solution of the critical wrinkling strain and wavelength for equi-biaxially stressed shell/core spheres. When the director is in-plane aligned, leading to primary uniaxial expansion upon heating, the core–shell usually buckles into stripes. For general spatial director alignment, the ultimate wrinkling patterns depending on the anisotropy state of spontaneous strains, can be hexagonal, parallel bead-chain, stripe, herringbone, labyrinth or hybrid. Lastly, we provide director-affected phase diagrams on pattern selection, which could be used to quantitatively guide the effective design of morphology-related smart surfaces such as anticounterfeiting system.